Advances in Artificial Systems for Logistics Engineering III - Hu, Zhengbing; Zhang, Qingying; He, Matthew (Lecture Notes on Data Engineering and Communications Technologies, 2023)
XVIII, 1094 p. 393 illus., 273 illus. in color.